A Physical Vulnerability to Climate Change Index: Which are the most vulnerable developing countries? - Mathilde Closset; Sosso Feindouno; Patrick Guillaumont; Catherine Simonet (Fondation pour les études et recherches sur le développement international (FERDI), 2018)
The recognition of climate change as a dominant issue for the global economy and policy has led to a search for resources for financing mitigation and adaptation. While raising funds for mitigation and for adaptation meet similar problems, their allocation between countries cannot be ruled by the same criteria. For the concessional funds devoted to adaptation allocation criteria should specifically reflect the adaptation needs of the recipient countries (beside their level of income and their capacity to effectively use the funds). An appropriate indicator of vulnerability to climate change is then required for guiding the allocation of adaptation resources. Not any indicator of vulnerability to climate change can fit this purpose..../...
Keywords: 330